Plasmid replication initiator protein RepD increases the processivity of PcrA DNA helicase. - Soultanas, P (1999)
The replication initiator protein RepD encoded by the Staphylococcus chloramphenicol resistance plasmid pC221 stimulates the helicase activity of the Bacillus stearothermophilus PcrA DNA helicase in vitro. This stimulatory effect seems to be specific for PcrA and differs from the stimulatory effect of the Escherichia coli ribosomal protein L3. Whereas L3 stimulates the PcrA helicase activity by promoting co-operative PcrA binding onto its DNA substrate, RepD stimulates the PcrA helicase activity by increasing the processivity of the enzyme and enables PcrA to displace DNA from a nicked substrate. The implication of these results is that PcrA is the helicase recruited into the replisome by RepD during rolling circle replication of plasmids of the pT181 family.